The Suitability of Fatha Clay Deposits for Clay Bricks Industry in Zurbatiya Area, Eastern Iraq - Al- Fraji, Yasmin Ibraheem; Al-Khafage, Satar Jabar (Iraqi Journal of Science, 2023)
This research aims to study the suitability of the Fatha Formation clay deposits for the brick industry in the Zurbatiya area, Wasit Government. Two sites (Al-Salam police station and Al-Taff station) were selected. The clay deposits were subjected to particle size analysis, atterberg limits, chemical and mineralogical analyses. The samples have 31.45% clay, 52.91% silt, and 15.64% sand. Chemical analyses revealed that SiO2 and CaO are the clay deposits’ main components, indicating the high content of quartz and calcium carbonate. The mineralogical analysis by XRD techniques indicated that quartz, calcite, feldspar, gypsum, and dolomite are the non-clay minerals; Kaolinite, illite, palygorskite and chlorite are the most clay minerals, followed by the mixed layer (montmorillonite-chloride). Clay brick samples were formed, dried and then fired using a particular firing program. The produced bricks have good water absorption (20-24.06%), compressive strength (36.23-41.63 N/mm2), and efflorescence (moderate – slight to nill). The properties of the produced clay bricks agree with the requirements of class A and B of the Iraqi Standard Specifications No.25,1993, British (BS 3921, 1985 ), and American Standard (ASTM C10, 2010).